MODERN TECHNOLOGY IN EDUCATION - Khalilova Shokhista Mukhammadi qizi,; Turopova Shabbona Bxodir qizi, (TADQIQOTLAR, 2026)
Abstract (English) This thesis examines the role of modern technology in contemporary education and  its  influence  on  teaching  methodology,  learner  autonomy,  and  academic performance. The study analyzes digital learning environments, artificial intelligence, online  educational  platforms,  and  interactive  technologies  that  contribute  to  the modernization  of  education  systems.  Comparative  and  pedagogical  approaches  are used to evaluate the advantages and limitations of technology-assisted learning. The paper also highlights the practical significance of digital literacy and technological integration  in  higher  education  institutions.  The  findings  demonstrate  that  modern technology  not  only  improves  accessibility  and  communication  but  also  enhances critical thinking, independent learning, and collaborative skills among students.